Temperature‐Insensitive High Strain in Lead‐Free Bi0.5(Na0.84K0.16)0.5TiO3–0.04SrTiO3 Ceramics for Actuator Applications. Issue 12 (26th August 2015) - Malik, Rizwan Ahmed; Hussain, Ali; Maqbool, Adnan; Zaman, Arif; Ahn, Chang‐Won; Rahman, Jamil Ur; Song, Tae‐Kwon; Kim, Won‐Jeong; Kim, Myong‐Ho
Abstract : Lead‐free piezoelectric ceramics, 0.96[Bi0.5 (Na0.84 K0.16 )0.5 1− x Li x (Ti1− y Nby )O3 ]–0.04SrTiO3 (BNKLiTN–ST) with x, y = 0–0.030, were synthesized by solid‐state reaction method. X‐ray diffraction patterns indicated that Li and Nb successfully diffused into the BNKT–ST lattice and formed a pure perovskite structure with x, y ≤ 0.025. Increasing the Li and Nb contents ( x, y = 0.020) induced a phase transformation from the coexistent rhombohedral–tetragonal phases for pure BNKT–ST ceramics to a pseudocubic phase, resulting in degradation of the remnant polarization and coercive field. However, the field‐induced strain was markedly enhanced at x, y = 0.020, giving rise to a giant dynamic piezoelectric constant ( d 33 * = S max / E max = 800 pm/V). Furthermore, the temperature dependence of the field‐induced strain response showed temperature‐insensitivity up to 120°C. To explore its potential for device applications, a 10‐layered stack‐type multilayer actuator was fabricated from the optimal composition ( x, y = 0.020). This actuator showed a large S max / E max of 600 pm/V at a relatively low driving field of 4.5 kV/mm suggesting highly promising results in lead‐free BNT‐based ceramics.